Reassessing the Nusantara Capital Authority: A Conflict with Indonesia’s Regional Autonomy Framework - al Arif, M. Yasin; Indra, Gandhi Liyorba (Sharia and Law Faculty, 2024)
This study examines the governance design of the Nusantara Capital Authority (Otorita Ibu Kota Nusantara), as established in Law No. 21 of 2023 amending Law No. 3 of 2023 concerning the Capital City of the State. The objective of this research is to assess whether the governance design of the Nusantara Capital Authority aligns with the principles of regional autonomy and to propose a future governance concept for the Nusantara Capital Authority. This research adopts a normative juridical approach, using statutory and conceptual methods, and utilizes secondary data consisting of primary, secondary, and tertiary legal materials. The findings indicate that the governance structure established under the IKN Law does not conform to the principle of regional autonomy, and as such, the Nusantara Capital Authority cannot be classified as a special regional government. The Nusantara Capital Authority does not possess the independent authority to manage its governmental affairs, as in the case of autonomous regions. Based on these findings, the author proposes a governance design for the Nusantara Capital Authority as an administrative area with the status of a Special Zone, which would exercise authority in the preparation, development, and relocation of the Capital City. Therefore, the recent amendments to the IKN Law have not altered the governance design of the Nusantara Capital Authority, which continues to maintain its status as a special region, despite not being in line with the principle of regional autonomy. Penelitian ini mengkaji desain tata kelola Otorita Ibu Kota Nusantara (Otorita Ibu Kota Nusantara), sebagaimana ditetapkan dalam UU No. 21 Tahun 2023 yang mengubah UU No. 3 Tahun 2023 tentang Ibu Kota Negara. Tujuan dari penelitian ini adalah untuk menilai apakah desain tata kelola Otorita Ibu Kota Nusantara telah sesuai dengan prinsip-prinsip otonomi daerah dan untuk mengusulkan konsep tata kelola Otorita Ibu Kota Nusantara di masa depan. Penelitian ini menggunakan pendekatan yuridis normatif, dengan menggunakan metode perundang-undangan dan konseptual, serta menggunakan data sekunder yang terdiri dari bahan hukum primer, sekunder, dan tersier. Hasil penelitian menunjukkan bahwa struktur pemerintahan yang dibentuk berdasarkan UU IKN tidak sesuai dengan prinsip otonomi daerah, sehingga Otoritas Jasa Keuangan tidak dapat diklasifikasikan sebagai pemerintah daerah khusus. Otoritas Modal Nusantara tidak memiliki kewenangan yang mandiri untuk mengelola urusan pemerintahannya, seperti halnya daerah otonom. Berdasarkan temuan ini, penulis mengusulkan desain tata kelola Otoritas Ibu Kota Nusantara sebagai wilayah administratif berstatus Kawasan Khusus, yang akan menjalankan kewenangan dalam penyiapan, pembangunan, dan pemindahan Ibu Kota. Oleh karena itu, amandemen UU IKN yang dilakukan baru-baru ini tidak mengubah desain tata kelola Otoritas Ibu Kota Nusantara, yang tetap mempertahankan statusnya sebagai kawasan khusus, meskipun tidak sejalan dengan prinsip otonomi daerah.